An electrochemical aptasensor for detection of Helicobacter pylori based on AuNPs and AgNPs-GO nanoparticles - You, Xiaojuan; Shao, Mingyi; Wang, Huadong; Zhu, Rui; Liu, Xinwei; Dong, Lei; Gong, Yuesheng; Li, Yongwei (Frontiers in Bioengineering and Biotechnology, 2025)
Helicobacter pylori is one of the main causes of gastritis and gastric ulcer. Early detection of H. pylori is of great significance for the prevention of gastric cancer. Herein, a sensitive electrochemical aptasensor using AgNPs-GO as redox probes was established for the specific detection of H. pylori in blood serum and stool samples. Firstly, AgNPs-GO nanocomposites were obtained by in-situ reduction of AgNPs on graphene oxide (GO) surface with glucose as reducing agent, in which AgNPs showed good biocompatibility and chemical stability, as well as redox property, and GO provided a large surface area to assemble a large number of AgNPs. Subsequently, the electrodeposition of AuNPs further improved the conductivity of the aptasensor. Additionally, the streptavidin was introduced into the aptasensor to effectively bind the biotin-modified aptamers. In this way, aptamers could be tethered to the surface through SA-biotin linkage, and H. pylori was selectivly binded by the aptamers subsequently. Under optimal conditions, the aptasensor could detect H. pylori in a wide concentration range (101 CFU mL−1–108 CFU mL−1) with a low detection limit of 3 CFU mL−1. What’s more, the developed method showed excellent performance in practical application, which provided a promising possibility for the detection of other pathogens in clinical diagnosis.